Perancangan Prototype Building Management System untuk Air Conditioning Berbasis Iot - Nurnadiyah Syuhada; Arief Taufikurrahman; Arino Bemi Sado (Jurnal Teknologi Informasi dan Multimedia, 2025)
This study aims to design, evaluate, test, and assess a prototype Internet of Things (IoT)-based building management system for air conditioning (AC) control in a campus building. The research background stems from the need for a system that can manage temperature more effectively, aligning with the demands of sustainability in energy management. The methodology employed in this study involves the development of a system using an ESP32 microcontroller, integrated with an Infrared (IR) transmitter and an LDR sensor. Testing was conducted to evaluate the performance of the IR transmitter in detecting signals at various distances (1 to 5 meters) and directions (straight, left, and right), as well as to measure the accuracy of the LDR sensor at a distance of 2 meters. The test results revealed that the IR transmitter achieved optimal detection performance at a distance of 1 meter, with significant degradation at greater distances. Conversely, the LDR sensor demonstrated 100% accuracy at a distance of 2 meters. The study concludes that the IoT-based AC control system designed not only enhances temperature management efficiency but also improves user comfort, with the potential for broader application in building management systems in the future.